2016
DOI: 10.4103/2008-7802.190598
|View full text |Cite
|
Sign up to set email alerts
|

Life psychosocial stresses and coronary artery disease

Abstract: Background:It is hypothesized that the impacts of life events accumulate and can trigger and promote atherosclerosis in susceptible individuals. In the current study, the correlation of total life stressors during 1 year was investigated relative to coronary artery disease (CAD).Methods:The study population consisted of 148 males and 152 females aged 35–76 years. The subjects were classified as CAD cases and controls according to the results of coronary angiography. The severity of CAD was scored on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Exposure to stressful life as assessed by the Holmes–Rahe Questionnaire recorded 9.4%, 3.8%, 59.4%, and 27.4% had low, normal, moderate, and high stress levels, respectively. In addition, 47.5% of patients with both moderate and high stress levels had other risk factors, such as low HDL level and illicit drug use, indicating a consistent result with the study by Bagheri et al ( 27 ), which showed that total psychological stress is correlated with the existence and severity of CAD considerably, but the correlation was not independent.…”
Section: Discussionsupporting
confidence: 88%
“…Exposure to stressful life as assessed by the Holmes–Rahe Questionnaire recorded 9.4%, 3.8%, 59.4%, and 27.4% had low, normal, moderate, and high stress levels, respectively. In addition, 47.5% of patients with both moderate and high stress levels had other risk factors, such as low HDL level and illicit drug use, indicating a consistent result with the study by Bagheri et al ( 27 ), which showed that total psychological stress is correlated with the existence and severity of CAD considerably, but the correlation was not independent.…”
Section: Discussionsupporting
confidence: 88%
“…Accumulating evidence indicates that chronic stress, especially chronic psychological stress, is a critical risk factor for atherosclerotic diseases (Kaplan et al, 1983; Rozanski et al, 1999; Empana et al, 2005; Bagheri et al, 2016). The mechanisms by which chronic stress factors contribute to the development of atherosclerosis are always the research focus (Empana et al, 2005; Everson-Rose et al, 2014; Peplinski et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is an important cardiovascular condition (1), causing 7.4 million deaths annually worldwide (2). As a multifactor disease, CAD is associated with upwards of 250 various risk factors (3). Some of these risk factors are hypertension, hyperlipidemia, diabetes, age, sex, obesity, smoking, and positive family history.…”
Section: Introductionmentioning
confidence: 99%